Complete genetic sequence of 15 novel HLA‐H alleles. (2nd March 2020) - Paganini, Julien; Dallas, Peter; Chiaroni, Jacques; Sayer, David; Di Cristofaro, Julie
Abstract : We describe the full gene sequences of 15 HLA‐H alleles.